Alexander and Anastayzia: the separation and search for family among Europe's displaced. Issue 4 (2nd October 2017) - Balint, Ruth
Abstract: In 1949, the child search branch of the International Tracing Service, set up after the war by the Red Cross and the Allies, began a search for the mother of a four year old boy, born to a forced labourer and left at a hospital in Rottenmunster at 8 months old. His file records first his abandonment, then his mother's strong resistance to external pressure to sign his adoption papers. His later attempts to trace his mother is also recorded. Taken together, the records shed light on the history of Nazi slave labour, lost children, forced adoptions, exile and the search for identity that connected episodes of displacement for many DPs that ended up in Australia. This article examines this history, and also considers the role of the archive as a powerful source for both enabling and disabling the search for family in the decades following the Second World War.